(untitled) (JURNAL ADMINISTRASI BISNIS, 2017)
Spiritual Leadership is a leader who can apply spiritual values into the practice of daily leadership. job satisfaction is a set of employee feelings about the fun or the absence of their work. The purpose of this study is to determine the influence of spiritual leadership on job satisfaction at PT. Bank Syariah Mandiri KC Manado. Methods of data collection using questionnaires and interviews. Analytical tool is the product moment correlation and simple linear regression to know the correlation or influence of the variable. The result of correlation shows the relationship of spiritual leadership to job satisfaction is moderate. However, hypothesis testing shows there is a positive influence between spiritual leadership and job satisfaction. Simple regression results show leaders have a spiritual leadership that impact on employee job satisfaction. The conclusion that can be taken from this research is there is positive and significance influence between spiritual leadership with job satisfaction at PT. Bank Syariah Mandiri KC Manado. The advice of this research is to always maintain the spiritual leadership of a leader because it is proven to increase job satisfaction from employees. Key : spiritual leadership, Job Satisfaction